2021
DOI: 10.3389/fimmu.2021.638144
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Numbers of HIV-Specific Poly-Functional CD8+ T Cells With Stem Cell-Like and Follicular Homing Phenotypes in HIV-Exposed Seronegative Individuals

Abstract: HIV-specific CD8+ T cells are known to play a key role in viral control during acute and chronic HIV infection. Although many studies have demonstrated the importance of HIV-specific CD8+ T cells in viral control, its correlation with protection against HIV infection remains incompletely understood. To better understand the nature of the immune response that contributes to the early control of HIV infection, we analyzed the phenotype, distribution and function of anti-viral CD8+ T cells in a cohort of HIV-expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…It is a robust predictor of T-cell efficacy in promoting protective immune response 40 . Studies on the HESN population have also revealed that the elevated levels of HIV-specific polyfunctional CD8+ T-cells and associated effector molecules are responsible for robust virus-inhibiting and keeping the plasma viral load undetectable 41 . Thus, we next evaluated the PCS-induced T-cell polyfunctionality, which is based on PCSstimulated T-cell's ability to secrete cytokines.…”
Section: Mepcs-mrna Lnp Generates a Pcs-specific T-polyfunctional Imm...mentioning
confidence: 99%
“…It is a robust predictor of T-cell efficacy in promoting protective immune response 40 . Studies on the HESN population have also revealed that the elevated levels of HIV-specific polyfunctional CD8+ T-cells and associated effector molecules are responsible for robust virus-inhibiting and keeping the plasma viral load undetectable 41 . Thus, we next evaluated the PCS-induced T-cell polyfunctionality, which is based on PCSstimulated T-cell's ability to secrete cytokines.…”
Section: Mepcs-mrna Lnp Generates a Pcs-specific T-polyfunctional Imm...mentioning
confidence: 99%
“…We found significantly elevated frequencies of CXCR5 + CD8 T cells and polyfunctional T cells, with stem cell likeness in HESN individuals. In addition, we also demonstrated a potent in vitro viral inhibition activity in the HESN population compared to HIV-infected and HIV-unexposed counterparts ( 60 ). To our knowledge, this is the first study reporting higher frequencies of Tfh and CXCR5 + CD8 + T cells in HESN cohorts from India.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to asymptomatic patients, highly-exposed seronegative individuals show a readily detectable response that is significantly stronger than in healthy and unexposed donors [ 23 , 49 , 50 ]. Polyfunctional T cell responses in highly-exposed seronegative individuals has also been described in the context of HIV [ 51 ], which correlated to people resistant to infections [ 52 ]. Whether this type of T cell responses in the absence of antibodies will be able to protect from SARS-CoV-2 infection or severe disease remain to be determined.…”
Section: T Cell Responses In the Convalescent Phasementioning
confidence: 99%